F2MoC: A Preliminary Product Line DSL for Mobile Robots - Durelli, Rafael S.; Durelli, Vinicius H. S. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2012: Anais do VIII Simpósio Brasileiro de Sistemas de Informação, 2012)
SPL and MDD have been drawing increased attention from the software community. In the literature it is possible to find a set of articles that apply MDD techniques to assist the development of a SPL. Objectives: To show how to create a DSL based on a feature model. Methods: A SPL and MDD techniques were used to create a DSL. Results: A DSL was developed in order to assist the development of the mobile robots. Conclusions: Advantages can be gained from using the DSL: (i) an easier instantiation of SPL members; (ii) it is possible for the engineers to focus on an high level model (i.e., features model), obviating the need of dealing with platform-specific issues; (iii) source code is generated automatically from this high level model.